ROYALTI DAN HAK EKONOMI MUSISI: TINJAUAN TERHADAP SISTEM KOLEKTIF MANAJEMEN DI INDONESIA - Ghefyra, Rahma; Rohmatul Ummah, Siti Kamilah Fitriah; Amrullah, Ulul Abshor; Alfatih, Zaidi Hamzah; Fatahillah, Ikhwan Aulia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The protection of musicians' economic rights through the royalty management system is a crucial element in creating a fair and sustainable music industry ecosystem in Indonesia. This study aims to analyze the effectiveness of the collective royalty management system for songs and/or music based on the national legal framework, specifically Law No. 28 of 2014 on Copyright and Government Regulation No. 56 of 2021. The approach used is juridical normative, with a qualitative analysis method applied to primary and secondary legal materials. The findings indicate that, although the collective management system involving Collective Management Organizations (LMK) and the National Collective Management Organization (LMKN) has a strong legal foundation, its implementation still faces several challenges, such as overlapping authority, infrastructure limitations, and the lack of outreach to musicians, especially independent musicians. On the other hand, reform efforts through strengthening regulations, utilizing technology such as the Song and Music Information System (SILM), and enhancing transparency and accountability of LMKN show positive steps towards a more professional system. Collaboration between the government, royalty management organizations, and the musician community is key to achieving effective and adaptive economic rights protection in response to the dynamics of the digital music industry.